Effect of secretin on plasma motilin in man. Issue 6 (June 1977) - Mitznegg, P; Bloom, S R; Domschke, W; Haecki, W H; Domschke, S; Belohlavek, D; Wünsch, E; Demling, L
Abstract : Graded doses of 0-1, 0-3, 0-9, and 2-7 clinical units/kg/h of pure synthetic secretin were infused over 60 minute periods in six healthy volunteers. Duodenal bicarbonate output and pH were recorded and plasma secretin and motilin levels were measured by radioimmunoassay. During the infusions plasma motilin fell in a dose dependent manner to a nadir of 35%. This fall was linearly correlated with pancreatic bicarbonate output, whereas a non-linear correlation was observed between plasma motilin and both plasma secretin level and duodenal pH. It is suggested that plasma motilin levels are decreased by secretin-induced pancreatic bicarbonate juice flow. This may be important for the control of motilin secretion initiated by duodenal acidification and the concomitant delay in gastric emptying.